Gender and law in the Japanese imperium - Brooks, Barbara J., 1953-2013; Burns, Susan L., 1958- (University of Hawaiʻi Press, 2014)
"Collectively, the essays [in this volume] offer a new framework for the history of gender in modern Japan and revise our understanding of both law and gender in an era shaped by modernization, nation and empire-building, war, occupation, and decolonization"--Jacket, page [3]